Attempts to Deny Bunjevci of backa (Vojvodina) the Right to Belong o the Croat Nation - Černelić, Milana (1997)
The introductory part of the article deals with basic data on history and ethnic structure of the province of Vojvodina, with special emphasis on the immigration of the Croat population in the region of backa and the ethnic changes in 20th century in the area.
The short account of the basic characteristics of the state of Kingdom of Serbs, Croats and Slovenes provides a perception of the political and social scene in which manipulations with the ethnicity of the Croat group Bunjevci occured. The tendency to neutralize Croats started very soon in the new state through the so called nationalisation of Vojvodina. Under the cover of the common Yugoslav name for three people living in one state, three basic forms of manipulatios with the ethnic name of Bunjevci came to light: 1. Neutralization of Bunjevci by emphasizing their distinctiveness: they are neither Serbs nor Croats; 2. Bunjevci can be both Serbs and Croats, which is the matter of individual choise, because both Serbs and Croats are in fact Yugoslavs; 3. Denial of the Croat ethnicity of Bunjevci, through manipulations with their religious belonging, in claim that Bunjevci are Serbs of Catholic religion.
Manipulations of the kind can be found in different forms in various published sources. The author demonstrates these attempts through quotations from the available and relevant sources. On the basis of the documents the author reaches the conclusions that writings of the kind in local newspapers reflected the attempts that had been initiated in certain Serbian scientific circles, whose intention was to prove that Bunjevci were Serbs who had been converted to Catolicism at one point in the past, or at least to persuade them to neglect their Croat etnicity. The author also refers to the reactions at the attempts that appeared in other local newspapers, which were definite about the Croatian ethnic origin of Bunjevci. In the last chapter she pionts to the new attempts to manipulate with the ethnic name of Bunjevci as well as Šokci, which is another Croat ethnic group in backa.
Projekt MZOS
ENG